2018
DOI: 10.1007/s12035-018-0868-4
|View full text |Cite|
|
Sign up to set email alerts
|

Peripheral and Central Effects of Memantine in a Mixed Preclinical Mice Model of Obesity and Familial Alzheimer’s Disease

Abstract: There is growing evidence that obesity associated with type 2 diabetes mellitus (T2DM) and aging are risk factors for the development of Alzheimer's disease (AD). However, the molecular mechanisms through which obesity interacts with β-amyloid (Aβ) to promote cognitive decline remains poorly understood. Memantine (MEM), a N-methyl-D-aspartate receptor antagonist, is currently used for the treatment of AD. Nonetheless, few studies have reported its effects on genetic preclinical models of this neurodegenerative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 54 publications
2
12
1
Order By: Relevance
“…Besides, they reported that Memantine—a drug which is currently used in AD treatment- showed an ameliorating effect on T2DM. This is in accordance with results published by our research group and others, where the benefits of Memantine administration were demonstrated in a mixed murine model of T2DM and AD (Sato and Morishita, 2013; Shinohara and Sato, 2017; Ettcheto et al, 2018b; Deng et al, 2019).…”
Section: Towards Brain Insulin Resistance In Late Onset Alzheimer’s Dsupporting
confidence: 93%
“…Besides, they reported that Memantine—a drug which is currently used in AD treatment- showed an ameliorating effect on T2DM. This is in accordance with results published by our research group and others, where the benefits of Memantine administration were demonstrated in a mixed murine model of T2DM and AD (Sato and Morishita, 2013; Shinohara and Sato, 2017; Ettcheto et al, 2018b; Deng et al, 2019).…”
Section: Towards Brain Insulin Resistance In Late Onset Alzheimer’s Dsupporting
confidence: 93%
“…Indeed, metabolic dysfunction has been widely hypothesized to be a key mechanism by which obesity induces neural deficits and increases AD risk (O'Brien et al, 2017;Pugazhenthi et al, 2017;Alford et al, 2018). Consistent with this position, previous work has shown interventions that reduce obesity in transgenic mouse models of AD also improve behavioral and pathological outcomes (Maesako et al, 2012;Walker et al, 2017;Yeh et al, 2017;Ettcheto et al, 2018). However, the current findings are not supportive of direct associations between improved metabolic profile and reduced AD-related indices.…”
Section: Discussioncontrasting
confidence: 59%
“…As such, this mechanism helps to explain the cognitive-improving effects of memantine, an NMDA receptor antagonist, in some AD patients (Parsons et al 2007). In support of this, AβPP/PS1 mice fed a HFD followed by treatment with memantine saw significant reductions in insulin resistance, neuroinflammation, and cognitive deficits (Ettcheto et al 2018). Alternatively, a HFD has been shown to decrease NMDA receptor subunit GluN2B leading to desensitization that may account for cognitive deficits (Valladolid-Acebes et al 2012).…”
Section: Discussionmentioning
confidence: 84%